Development of a mechanical weeder and experiment on the growth, yield and quality of rice - Jiao, Jinkang; Wang, Zhimin; Luo, Haowen; Chen, Gaolong; Liu, Hailong; Guan, Jinjie; Hu, Lian; Zang, Ying (International Journal of Agricultural and Biological Engineering, 2022)
Weed control in paddy fields is a worldwide problem and mechanical weeding will become a major weeding method in non-chemical weeding. A mechanical weeder was designed and tested to improve the efficiency of mechanical weeding and reduce the application of herbicides in this study. The weeding equipment is equipped with three sets of inter-row weeding parts which include ground-contoured-following pressing-grass float (GPF), weeding roller, and so on. The weeding principle of weeding part is that the weeding equipment enters the inter-row area with weeder moving forward, then the GPF overwhelms the weeds in the inter-row area to improve the probability that the weeding roller behind the GPF pressed the overwhelmed weeds into the soil. The effects of weeding methods on the plant height, grain yield and quality attributes were investigated in a two-seasonal field experiment. Three weeding methods were applied in the present study: no-weeding, chemical weeding and mechanical weeding. The results of the two-seasonal field experiment showed that the average weeding rates of mechanical weeders were 87.10% and 87.61% respectively. In both seasons, there was no significant difference among weeding methods on plant height at the early growth stage of rice after weeding, but weeding methods had significant effect on plant height at the late growth stage. The plant height of mechanical weeding was higher at the late growth stage. Weeding methods had significant effects on grain yield, grain number per panicle, seed-setting rate, 1000-grain weight and shoot dry matter accumulation (p<0.05), however there was no remarkable effect on rice quality and other attributes (p>0.05). Grain yield of mechanical weeding was significantly higher than that of no-weeding. There was no significant difference between chemical weeding and mechanical weeding. It can be concluded from the two-seasonal experiment that mechanical weeding had the same effect as chemical weeding on grain yield and rice quality. Keywords: weeder, paddy field, mechanical weeding, grain yield, rice quality DOI: 10.25165/j.ijabe.20221503.6978 Citation: Jiao J K, Wang Z M, Luo H W, Chen G L, Liu H L, Guan J J, et al. Development of a mechanical weeder and experiment on the growth, yield and quality of rice. Int J Agric & Biol Eng, 2022; 15(3): 92–99.